Diplomasi Koersif Amerika Serikat Terhadap Indonesia Melalui Embargo 1991-2005 - Ira Rizka Aisyah Lubis (PERSPEKTIF, 2022)
This article aims to analyze the effectiveness of the coercive diplomacy carried out by the United States against Indonesia. These coercive diplomatic actions are in the form of embargoes, such as arms embargoes and IMET Ban. This study uses qualitative research methods using secondary data. The long duration of the IMET Ban and the arms embargo that occurred more than once made the United States' coercive diplomacy towards Indonesia look ineffective. Therefore, this study raises the research question "Why is the United States' coercive diplomacy towards Indonesia through the Arms Embargo and IMET Ban not effective?" and will be answered using the variables provided by Tom Sauer in the concept of the effectiveness of coercive diplomacy. Seeing the current conditions, if Indonesia buys military equipment from Russia, such as the Su-35, it will be subject to sanctions, so this research can conclude that the coercive diplomacy carried out by the United States against Indonesia is not effective.